2021
DOI: 10.1021/acssuschemeng.1c01396
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Emission from Greenish to Blue via Chemical Composition Modulation in Solid Solutions (Sr1–yCay)2Sb2O7:Bi3+ under near-UV Light Excitation

Abstract: The Bi3+ ion, with an exposed 6s2 energy level sensitive for an external coordination environment, possesses complex and intriguing luminescent properties in various host lattices. Herein, we successfully prepared a new type of antimonate phosphor (Sr1–y Ca y )2Sb2O7:Bi3+ with controllable color emitting properties from greenish to blue stimulated by near-ultraviolet (UV) light. There are two emitting bands at 495 and 528 nm that go along with two crystallographic distinct Bi3+ sites in the Sr2Sb2O7 host. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
2
13
0
5
Order By: Relevance
“…Usually, Bi + shows emission in the near-infrared region, Bi 2+ shows strong red–orange emission, and Bi 3+ emits strongly in the UV to green regions . Many Bi 3+ -doped phosphors excited with n-UV show similar blue luminescence properties. ,, Thus, the deep-blue emission is attributed to Bi 3+ . X-ray photoelectron spectroscopy (XPS) spectra of Sc 2 Si 2 O 7 :Bi 3+ and pure α-Bi 2 O 3 (99.99%) as a reference are shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, Bi + shows emission in the near-infrared region, Bi 2+ shows strong red–orange emission, and Bi 3+ emits strongly in the UV to green regions . Many Bi 3+ -doped phosphors excited with n-UV show similar blue luminescence properties. ,, Thus, the deep-blue emission is attributed to Bi 3+ . X-ray photoelectron spectroscopy (XPS) spectra of Sc 2 Si 2 O 7 :Bi 3+ and pure α-Bi 2 O 3 (99.99%) as a reference are shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…22 Many Bi 3+doped phosphors excited with n-UV show similar blue luminescence properties. 20,23,24 Thus, the deep-blue emission is attributed to Bi 3+ . X-ray photoelectron spectroscopy (XPS) spectra of Sc 2 Si 2 O 7 :Bi 3+ 1a), which is attributed to the change in the crystal field strength and nephelauxetic effect around Bi 3+ with a reduction in the ionic radius.…”
Section: ■ Introductionmentioning
confidence: 97%
“…It has been reported that n-UV LED chips + RGB phosphors (strategy three) is an effective method to solve the above problems, which can achieve whole-visible-spectrum white lighting. 12,13 However, this kind of pc-WLED still has the defect of cyan gap. If this problem can be solved, the lighting quality will undoubtedly be greatly improved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, this combination of pc-WLED has a low Ra (<80) due to the lack of red and cyan light in the spectrum, which does not meet the requirements of high-quality white light illumination. The second strategy also has the problem of intense blue light. It has been reported that n-UV LED chips + RGB phosphors (strategy three) is an effective method to solve the above problems, which can achieve whole-visible-spectrum white lighting. , However, this kind of pc-WLED still has the defect of cyan gap. If this problem can be solved, the lighting quality will undoubtedly be greatly improved. , Therefore, it is necessary to develop a high-efficiency cyan-emitting phosphor to close the cyan gap.…”
Section: Introductionmentioning
confidence: 99%
“…However, the investigation on its self‐host emission is not enough. Although Zhao et al prepared the tuning‐emission (Sr 1−y Ca y ) 2 Sb 2 O 7 :Bi 3+ phosphors and further considered that the luminescent behaviors originated from the featured emission of 1 S 0 → 3 P 1 (Bi 3+ ), 29 we identified that the self‐host emitting Ca 2 Sb 2 O 7 phosphors could reveal a strong pure blue emission with high color purity (90.78%) and QY (60.04%); and then it would exhibit color‐turning behaviors with the change of Sr 2+ ion content. Furthermore, some characterizations of crystal structure, elemental composition, morphology, thermal stability, luminescent dynamics, density functional theory (DFT), and luminescent efficiency for the resultant samples would be also investigated in detail in this work.…”
Section: Introductionmentioning
confidence: 99%